Well-being of older people in East Asia: The People's Republic of China, Japan, and the Republic of Korea - Hidehiko Ichimura; Xiaoyan Lei; Chulhee Lee; Jinkook Lee; Albert Park; Yasuyuki Sawada (Asian Development Bank (ADB), 2024)
East Asia is undergoing a rapid demographic transition and "super" aging. As a result of steadily decreasing fertility and increasing life expectancy, older people's proportion of the population and the old-age dependency ratio is rising across all countries in East Asia, particularly in the People's Republic of China (PRC), Japan, and the Republic of Korea (ROK). In this paper, we empirically investigate the well-being of older people in these three countries, using comparable microlevel data from the China Health and Retirement Longitudinal Study (CHARLS), the Japanese Study of Aging and Retirement (JSTAR), and the Korean Longitudinal Study on Aging (KLoSA). Specifically, we examine the depressive symptom scale as a measure of well-being and estimate the impact of four broad categories-demographic, economic, family-social, and health. The decomposition and simulation analysis reveals that although much of the difference in mean depression rates among countries can be explained by differences in the characteristics of older people in the three countries, there remain significant differences across countries that cannot be explained. In particular, even after accounting for a multitude of factors, older people in the ROK are more likely to be depressed than in the PRC or Japan.
Keywords: D1; I3; J14; 330; aging; well-being; depression; suicide; panel data